DIRECTIONS FOR IMPROVING THE PROCESS OF PERSONAL INCOME TAX FORECASTING (American Journal of Interdisciplinary Research and Development, 2024)
This article reflects the problems of foreign experience in forecasting tax revenues from personal income tax and a methodological approach to further improvement of this process.